Reducing gravity takes the bounce out of running - Polet, D. T.; Schroeder, R. T.; Bertram, J. E. A. (The Journal of Experimental Biology, 2018)
In gravity below Earth-normal, a person should be able to take higher leaps in running. We asked 10 subjects to run on a treadmill in five levels of simulated reduced gravity and optically tracked centre-of-mass kinematics. Subjects consistently reduced ballistic height compared with running in normal gravity. We explain this trend by considering the vertical take-off velocity (defined as maximum vertical velocity). Energetically optimal gaits should balance the energetic costs of ground-contact collisions (favouring lower take-off velocity), and step frequency penalties such as leg swing work (favouring higher take-off velocity, but less so in reduced gravity). Measured vertical take-off velocity scaled with the square root of gravitational acceleration, following energetic optimality predictions and explaining why ballistic height decreases in lower gravity. The success of work-based costs in predicting this behaviour challenges the notion that gait adaptation in reduced gravity results from an unloading of the stance phase. Only the relationship between take-off velocity and swing cost changes in reduced gravity; the energetic cost of the down-to-up transition for a given vertical take-off velocity does not change with gravity. Because lower gravity allows an elongated swing phase for a given take-off velocity, the motor control system can relax the vertical momentum change in the stance phase, thus reducing ballistic height, without great energetic penalty to leg swing work. Although it may seem counterintuitive, using less `bouncy` gaits in reduced gravity is a strategy to reduce energetic costs, to which humans seem extremely sensitive.